P089: Reducing preventable patient transfers from long-term care facilities to emergency departments: a scoping review. (May 2020) - Grant, K.; Lee, D.; Cheng, I.; Baker, G.
Abstract : Introduction: Emergency Department (ED) crowding is an international health system issue that is worsening. Further, ED crowding and "hallway medicine" has been identified as one of the most significant healthcare challenges currently facing Canadians. One contributor is preventable transfers from long-term care facilities (LTCFs) to Emergency Departments (EDs). In Canada, there were 63, 752 LTCF patient transfers to the ED in 2014, with 24% (15, 202) of them due to potentially preventable conditions. Each preventable transfer exposes patients to transport and hospital-related complications, and costs the healthcare system thousands of dollars. There have been many proposed and studied interventions aimed at alleviating the issue, but few attempts to assess and evaluate different interventions across institutions in a systematic manner. Methods: A scoping review of the literature using three electronic databases was conducted. A scoping review methodology was used due to the range of interventions and the heterogeneity in study design and outcome. Inclusion criteria included: studies on interventions designed to reduce transfers from LTCFs, studies that reported key outcomes such as number of ED transfers, and studies with a control or comparison group. Articles were screened by two independent reviewers (Cohen's k = 0.68), and study quality was assessed using the National Heart, Lung, Blood Institute quality assessment tools. Results: Findings were organized into five intervention types (telemedicine, outreach teams, interdisciplinary teams, integrated approaches, and other), and both a tabular and narrative synthesis was completed. Eleven studies had a good quality assessment rating, 13 studies had a fair rating, and two studies had a poor rating. Twenty out of the 26 studies reported statistically significant reductions in ED transfer rate, ranging from 10-70%. Interdisciplinary healthcare teams staffed within LTCFs were the most effective interventions. Conclusion: There are several promising interventions that have successfully reduced the number of preventable transfers from LTCFs to EDs, in a variety of health system settings. Further analysis of the relative resource requirements of each intervention, and practices that can enable successful implementation are needed to inform healthcare policy and administrative decision making. Widespread implementation of these interventions has the potential to considerably reduce ED crowding.